CHANG-ES. XXXV. Cosmic Ray Transport and Magnetic Field Structure of NGC 3556 at 3 GHz - Jianghui Xu; Yang Yang; Jiang-Tao Li; Guilin Liu; Judith Irwin; Ralf-Jürgen Dettmar; Michael Stein; Theresa Wiegert; Q. Daniel Wang; Jayanne English (The Astrophysical Journal)
Radio halos of edge-on galaxies are crucial for investigating cosmic ray propagation and magnetic field structures in galactic environments. We present VLA C-configuration S -band (2–4 GHz) observations of the spiral galaxy NGC 3556, a target from the Continuum Halos in Nearby Galaxies—an EVLA Survey. We estimate the thermal contribution to the radio emission from a combination of the H α and mid-IR data, and employ rotation measure synthesis to reveal the magnetic field structures. In our data, NGC 3556 exhibits a box-like radio halo extending nearly 7 kpc from the galactic plane. The scale height of the total S -band intensity in the halo is 1.68 ± 0.29 kpc, while that of the nonthermal intensity is 1.93 ± 0.28 kpc. Fitting the data to a 1D cosmic-ray transport model, we find advection to describe the cosmic-ray propagation within the halo better than diffusion, with advection speeds of 245 ± 15 km s ^−1 and 205 ± 25 km s ^−1 above and below the disk, respectively. The magnetic field is detected patchily across the galaxy, displaying a toroidal configuration in the rotation measure map. The mean equipartition magnetic field strength is approximately 8.3 μ G in the disk and 4.5 μ G in the halo. In addition, a bubble-like structure extends nearly 3 kpc into the southern halo, aligned with the polarized intensity and H α image, suggestive of superwinds generated by recent star formation feedback in the nuclear region.